2010
DOI: 10.1016/j.neuroimage.2010.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Body mass correlates inversely with inhibitory control in response to food among adolescent girls: An fMRI study

Abstract: Self-report and behavioral data suggest that impulsivity may contribute to the development and maintenance of obesity. Neuroimaging studies implicate a widespread neural network in inhibitory control and suggest that impulsive individuals show hypoactivity in these regions during tasks requiring response inhibition. Yet, research has not directly tested whether body mass correlates inversely with activation of these regions during response inhibition tasks. The present study used functional magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
379
9
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 461 publications
(445 citation statements)
references
References 52 publications
42
379
9
6
Order By: Relevance
“…The results of our study complement findings of two longitudinal fMRI studies, that investigated the link between neurobehavioural impulse control parameters and BMI (changes) in non-dieting subjects (Batterink et al, 2010;Kishinevsky et al, 2012). In the first study (Batterink et al, 2010) the authors measured reaction times and neural activity of subjects during a go-/nogo-task and correlated these measures with the BMI at baseline and one year later.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The results of our study complement findings of two longitudinal fMRI studies, that investigated the link between neurobehavioural impulse control parameters and BMI (changes) in non-dieting subjects (Batterink et al, 2010;Kishinevsky et al, 2012). In the first study (Batterink et al, 2010) the authors measured reaction times and neural activity of subjects during a go-/nogo-task and correlated these measures with the BMI at baseline and one year later.…”
Section: Discussionsupporting
confidence: 71%
“…Among psychological factors, impaired impulse control is believed to play an important role for obesity (e.g., McGuire et al, 2001;Masheb et al, 2002;Weller et al, 2008;Nijs et al, 2010;Batterink et al, 2010;Kishinevsky et al, 2012) as well as for other major health problems, such as drug addiction (e.g., Volkow et al, 2004;Goldstein et al, 2007;Barrós-Loscertales et al, 2011) and alcohol abuse (e.g., Li et al, 2009). The association of obesity and impulse control has been tested in behavioural studies that found that impulse control measured with delay discounting (DD) paradigms or questionnaires is negatively associated with body weight (Weller et al, 2008;Masheb et al, 2002;McGuire et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, activation of frontal inhibitory regions has been shown to correlate inversely with body mass index (BMI) when participants were instructed to inhibit their responses to appetizing food pictures in a go/no-go task. 22 All in all, these studies show that overweight women exhibit a greater response in rewardrelated regions in response to food cues than healthy-weight women.…”
Section: Introductionmentioning
confidence: 61%
“…Although the majority of studies investigating food reward-processing differences between obese versus healthy-weight participants have been conducted during hunger or moderate deprivation, 17,[20][21][22]27 the excess of energy intake in obesity is at least partly because of eating in the absence of hunger, also called nonhomeostatic eating. 28,29 Therefore, the current study seeks to investigate food reward-processing differences between overweight participants and healthy-weight ones while they are satiated.…”
Section: Introductionmentioning
confidence: 99%